Matrix structural analysis of multistorey three dimensional building frames - Alcantara, Pablo R. (1991)
A computer method for the structural analysis of multistorey building frames subjected to lateral loads is presented. The analysis includes the secondary effects specifically the P-delta and the effect of high axial compression load in column flexural stiffness but neglects axial and shear deformations in the members. St Venant and wrapping torsion of the members are assumed to be negligible compared to warping torsion of the building as a whole. The development of the structure stiffness matrix of order three times the number of storeys is based on the superposition of lateral stiffness of subframes in the principal axis directions of the building and assuming rigid body motion of building floors. lateral stiffness matrix of each frames are formed systematically by static condensation of the subframe stiffness matrix leaving only the lateral forces and deformations. From the method presented, a computer program (EQUASIS) is based and developed in Pascal language.